Smart Delivery and Controlled Drug Release with Gold Nanoparticles: New Frontiers in Nanomedicine - Voliani, Valerio; Signore, Giovanni; Nifosi, Riccardo; Ricci, Fernanda; Luin, Stefano; Beltram, Fabio (Recent Patents on Nanomedicine, 2012)
Discoveries in the field of nanotechnology are triggering a revolution in medicine, by providing a profusion of potential and actual applications of nanosized objects in the diagnosis and treatment of several diseases. This trend is also evident in the increasing number of patents recorded annually. In particular, nanoparticles able to find a target and release their payload upon a specific stimulus are highly attractive for the diagnostics and therapeutics, for example, of cancer and gene diseases. In this view, gold nanoparticles (AuNPs) stood out as suitable platforms for the development of efficient delivery and release systems. AuNPs are biocompatible, and can be easily synthesized and functionalized. The capability of tuning their size and geometry allows manipulating their optical and physical properties. Engineering their coating controls the stability, targeting and release features. In this review several patents concerning release strategies based on gold nanostructures are reported, together with a discussion about their operating processes and their mutual advantages and disadvantages.
Keywords: Biocompatibility